Comparison of running economy values while wearing no shoes, minimal shoes, and normal running shoes - Cochrum, R. G.; Connors, R. T.; Coons, J. M.; Fuller, D. K.; Morgan, D. W.; Caputo, J. L. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to quantify differences in running economy (RE) at 50 and 70% of each subject's velocity at VO2max (vVO2max) across barefoot and 2 mass, stack height, and heel-to-toe-drop controlled footwear conditions (minimal shoes and normal running shoes) in 9 recreational distance runners (mean age 26.8 ± 6.8 years). Over 3 days, subjects ran in one of the footwear conditions while RE (oxygen consumption) and step frequency were measured at each speed with a 5-minute rest between each trial. A 2-way repeated-measures multivariate analysis of variance (p = 0.05) and Bonferroni-adjusted follow-up analyses revealed that RE was not significantly different across footwear conditions at either speed. However, those running barefoot exhibited a higher step frequency than when running in minimal (50%, p = 0.007; and 70%, p < 0.001) and standard footwear conditions (70% only, p < 0.001). Higher step frequencies were also exhibited by those running in minimal versus standard footwear (70% only, p = 0.007). Thus, RE is not affected by footwear or running barefoot in those with experience running in minimal-type footwear. Significant adjustments in step frequency when alternative footwear was introduced may help explain why RE was statistically maintained during each footwear and speed condition across but not between subjects. Therefore, determination of footwear for the enhancement of RE should be based on individual physical characteristics and preferences rather than a global recommendation of an economical running shoe.